Partial Least Square Algorithm (PLS) with Technology Acceptance Model (TAM) in User Analysis of Public Health Center Management Information System (SIMPUS) Applications - Sri Mulyono Mulyono; Wahyul Amien Syafei; Retno Kusumaningrum (Scientific Journal of Informatics, 2023)
Purpose: The most important information system application at the health center is the health center management information system or can be called SIMPUS. The SIMPUS is an application program specifically designed to help facilitate recording of patient data, processing and presenting data into information in a short time. With the SIMPUS application, it is necessary to examine whether the application is very helpful for users in completing work at the public health center or Puskesmas. Therefore, the purpose of this study is to analyze the SIMPUS application users by combining the Partial Least Square (PLS) algorithm with the Technology Acceptance Model (TAM) method.Methods: SIMPUS application user analysis is carried out using a combination of the Partial Least Square (PLS) algorithm with the Technology Acceptance Model (TAM) method. The variables used are Perceived Usefulness, Perceived Ease of Use, Attitude Towards Using, Behavioral Intention to Use, and Actual System Use. Data collection techniques by distributing closed questionnaires and taking samples with the solvency formula. Sampling was carried out using a multistage random sampling technique, the number of 12 Puskesmas in each Puskesmas from the calculation results determined 40 samples.Result: From the statistical test results, the effect of the perceived usefulness on the ease of use has the highest level of influence, which obtaining a test value of 3.6. Furthermore, the effect of the attitude towards using on the behavioral intention to use has the lowest level of influence, which obtaining a test value of 1.2.Value: Analysis and testing of variables that influence user acceptance of the SIMPUS application using the Partial Least Square (PLS) algorithm and the Technology Acceptance Model (TAM) approach, that acceptance of the SIMPUS application is influenced by the level of usability and ease of use of the application.